Glucagon-like peptide-1: a potent regulator of food intake in humans. Issue 1 (1st January 1999) - Gutzwiller, J-P; Göke, B; Drewe, J; Hildebrand, P; Ketterer, S; Handschin, D; Winterhalder, R; Conen, D; Beglinger, C
Abstract : Background/Aims: Studies in animals suggest a physiological role for glucagon-like peptide-1-(7–36)-amide (GLP-1) in regulating satiety. The role of GLP-1 in regulating food intake in man has, however, not been investigated. Subjects—Sixteen healthy male subjects were examined in a double blind placebo controlled fashion. Methods: The effect of graded intravenous doses (0, 0.375, 0.75, and 1.5 pmol/kg/min) of synthetic human GLP-1 on food intake and feelings of hunger and satiety was tested in healthy volunteers. Results: Graded GLP-1 infusions resulted in a dose dependent reduction in food intake (maximal inhibition 35%, p<0.001 v control) and a similar reduction in calorie intake (32%; p<0.001). Fluid ingestion was also reduced by GLP-1 (18% reduction, p<0.01). No overt side effects were produced by GLP-1, but subjects experienced less hunger and early fullness in the period before a meal during GLP-1 infusion at the highest dose (p<0.05). Conclusions: Intravenous infusions of GLP-1 decrease spontaneous food intake even at physiological plasma concentrations, implying an important role for GLP-1 in the regulation of the early satiety response in humans.